Herb-Drug Interactions: An Insight into Cardiovascular Diseases Based on Case Reports - Batista, Cheila; R. Jesus, N.; M. Silva, Catia; P. Silva, Tiago; G. Campos, Maria (Cardiovascular & Hematological Agents in Medicinal Chemistry, 2016)
Cardiovascular patients frequently use herbal medicinal products, in order to contribute to the improvement of their chronic condition without medical intervention. However, they are likely to suffer from adverse effects from natural products and herb-drug interactions. In this work we present the results collected from a public campaign “Learning Health, among Plants and Medicines”, carried out by the Observatory of Herb-Drug Interactions (www.oipm.uc.pt), to alert cardiovascular patients and healthcare providers for the potential occurrence of herb-drug interactions with cardiovascular therapy. From the data received, it was highlighted the prevalence of certain natural products used by many cardiovascular patients in Portugal, particularly goji berries, green tea, mangosteen and rooibos that have significant cardiovascular effects. For this reason their intake should be carefully monitored in these patients. This prevalence of consumption suggests a pattern in their use in Portugal and a prevention of herb-drug interactions should be carried out by the health professionals. The ending results also indicate that there is still a lack of knowledge about the possible risks of herbal products intake, which may adversely affect the health of any patient. Thus becomes clear the value of the role of health professionals in the screening of such interactions.
Keywords: cardiovascular diseases